2017
DOI: 10.1002/adma.201700639
|View full text |Cite
|
Sign up to set email alerts
|

Clean Transfer of Large Graphene Single Crystals for High‐Intactness Suspended Membranes and Liquid Cells

Abstract: The atomically thin 2D nature of suspended graphene membranes holds promising in numerous technological applications. In particular, the outstanding transparency to electron beam endows graphene membranes great potential as a candidate for specimen support of transmission electron microscopy (TEM). However, major hurdles remain to be addressed to acquire an ultraclean, high-intactness, and defect-free suspended graphene membrane. Here, a polymer-free clean transfer of sub-centimeter-sized graphene single cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 34 publications
1
136
0
Order By: Relevance
“…Moreover, the interplay of surface tension between the two water phases (the droplet on the grid and the water underneath the second graphene sheet) causes local water turbulence. For these reasons, the approach yields a highly ruptured and crumbled second graphene layer, even if multilayer or monocrystalline graphene are used . Graphene deposited by the LAT and the touch‐down method onto a paper substrate reveal the difference in surface coverage between both methods (Figure f,g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the interplay of surface tension between the two water phases (the droplet on the grid and the water underneath the second graphene sheet) causes local water turbulence. For these reasons, the approach yields a highly ruptured and crumbled second graphene layer, even if multilayer or monocrystalline graphene are used . Graphene deposited by the LAT and the touch‐down method onto a paper substrate reveal the difference in surface coverage between both methods (Figure f,g).…”
Section: Resultsmentioning
confidence: 99%
“…We include here a concise overview of common GLC assembly methods. To our knowledge the most common method comprises the sandwiching of water between two TEM grids carrying graphene on a porous support film . As graphene is supported through the sample assembly procedure, this method has the largest chance of retaining graphene integrity, albeit at the cost of losing graphene flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examined under the VPP-Cs-corrector-coupled Titan Krios at 300 kV with phase shift ranging from 30 to 120 degrees, the SA specimens demonstrated monodispersed particles with high contrast that could be easily identified and automatically picked ( Figure 1A). We found that the single-crystalline graphene with monolayer of carbon atoms introduced very low background noise to the specimen and could also serve as a good reference for the assessment of the cryo-EM image quality and motion correction with its hexagonal lattice signal 23,24 . After motion correction of the raw movie stacks of the specimen, we calculated the Fourier transform of the motion-corrected micrographs.…”
Section: Preparation Of Frozen-hydrated Sa Specimen On Graphene Suppomentioning
confidence: 97%
“…Despite the rapid growth of bottom‐up method, industrial level production of graphene is still challenging. Mass production of highly conductive graphene sheets represents an essential step toward the extensive applications of graphene for LBs . Chemical reduction of GO is the most popular technique to prepare graphene with high yields.…”
Section: Preparation Of Carbon‐based Nanomaterialsmentioning
confidence: 99%